Modernism and fascism : the sense of a beginning under Mussolini and Hitler - Griffin, Roger 1948- (Palgrave Macmillan, 2007)
"It has been widely assumed that fascism was anti-modern, the sworn enemy of genuine culture: thus the Third Reich barbarically destroyed modernism, while fascism cynically harnessed the creativity of the artistic avant-garde and technocratic elite to reactionary ends. In contrast, Roger Griffin's Modernism and Fascism convincingly portrays fascism as a 'total' form of modernism in its own right. Like a modernist painting itself, this ambitious book transforms our understanding of the art, technology, social ethos, and politics of the first half of the twentieth century."--BOOK JACKET